Responsible management of shifts in work modes. volume 2 : values for post pandemic sustainability - Ogunyemi, Kemi; Onaga, Adaora I. (Emerald Publishing Limited, 2023)
The Covid 19 pandemic transformed the slow morphing of work modes into rapid shifts that heightened VUCA characteristics globally. The management of these shifts in work dynamics is the focus of the chapters in this volume. The variation of post-pandemic outcomes for businesses, from complete collapses to profit booms, easily motivates an interest in the values that influence truly positive outcomes. Also, the health sector, globally, has borne much of the brunt of the pandemic and needs to draw practical lessons to promote its adaptability and sustainability through future crises. Responsible Management of Shifts in Work Modes - Values for Post Pandemic Sustainability, Volume 2 looks at specific issues relating to ethical leadership, people management, resilience, and the management of consequences for business and healthcare systems. In the process, contributors identify challenges to and engage in in-depth discussions of work values that enrich people management. The necessary qualities needed to develop these work values both now and in the future are thus highlighted in the different chapters: both individual and organisational characteristics are explored while developing ways to promote responsible management through fairness to stakeholders and ethical leadership. As a post-pandemic future incorporates new realities distinct from the old normal and yet does not change the purpose of all responsible management, this book deliberates on the necessity of values, virtues, and skills to make the necessary work mode shifts in small, medium, and large organisations positively impactful for the future of humanity.
Keywords: Business ethics.; Personnel management.; Sustainability.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books